Diagnostic delay in adult-onset dystonia: Data from an Italian movement disorder center. Issue 3 (March 2015) - Macerollo, A.; Superbo, M.; Gigante, A.F.; Livrea, P.; Defazio, G.
Abstract Adult-onset dystonia (AOD) may manifest in focal forms (as blepharospasm, oromandibular dystonia, cervical dystonia, laryngeal dystonia, and hand dystonia) or in segmental forms. Time from onset of dystonia to diagnosis can be an indicator of the quality of care received during the diagnosis of AOD, likely reflecting factors associated with both the patient and their health system. Three previously reported single-center studies showed that diagnosis of AOD may be delayed for several years. Here, we examined the time lapse between onset and diagnosis in patients with different forms of AOD from an Italian movement disorder center. We found the time lapse between dystonia onset and diagnosis was very long for patients who developed AOD before 1980; and even in the most recent years reaching a correct diagnosis required more than year in almost half of cases. Our results suggest that the delay in diagnosis of adult-onset focal and segmental dystonia has improved over time, but remains unacceptable. The findings are a promising indicator of improvements in care of this uncommon disorder. However, education of patients and doctors is still needed.